Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3329/brj.v19i2.28168
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × Environment Interaction and Yield Stability Analysis in Hybrid Rice (Oryza sativa L.) By AMMI Biplot

Abstract: CORRECTION: Due to a number of formatting and layout issues, the PDF of this paper was replaced on 10th October 2016. The page numbers of this article have changed from 79-86 to 83-90.Assessing the adaptability and stability of promising rice genotypes is one of the important steps for accurate evaluation. This study determined the genotype × environment interaction (GEI) and stability performance of 12 promising rice genotypes in four environments during 2009 Aman season. The experiment used randomized comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 16 publications
(18 reference statements)
3
11
0
Order By: Relevance
“…The differences of mean square due to (environments + (Genotypes X Environments) were highly significant for all traits studied which exhibited that considerable interaction of all entries under different environmental conditions of years, locations and treatments in different years. The variances due to entries were showed to be highly significant for all the traits studied against pooled deviation which means the presence of sufficient genetic variability between the genotypes, Gill and Kumar (1989), Popovic et al, (2013), Selvi et al, (2015), Hamawaki et al, (2015), Akter et al, (2015)and Silva et al, (2016).…”
Section: Variation and Interactionmentioning
confidence: 87%
“…The differences of mean square due to (environments + (Genotypes X Environments) were highly significant for all traits studied which exhibited that considerable interaction of all entries under different environmental conditions of years, locations and treatments in different years. The variances due to entries were showed to be highly significant for all the traits studied against pooled deviation which means the presence of sufficient genetic variability between the genotypes, Gill and Kumar (1989), Popovic et al, (2013), Selvi et al, (2015), Hamawaki et al, (2015), Akter et al, (2015)and Silva et al, (2016).…”
Section: Variation and Interactionmentioning
confidence: 87%
“…Previously, studies comparing transgenic cultivars and non-transgenic recurrent parents have shown a significant difference between these cultivars in yield and quality traits [24,41,57]. Studies of hybrids of rice [16,58] and maize [59,60] have concluded that hybrid genotypes are not only high-yielding but also show stable performance in different environments. The ultimate objective of the current study was to compare the performance and stability of hybrids and inbred lines of cotton in different environments.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that GEI has significant effects on yield and quality traits in various crops [13][14][15][16]. Similarly, GEI research has long been of major interest to cotton breeders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of a crop is the result of the cultivar's genotype (G), the environment in which it grows (E), and the interaction between G and E (GEI) (Akter et al, 2015). Interaction between these two explanatory variables gives an insight towards the identification of the genotype suitable for specific environments, which may constitute good opportunities (Bornhofen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%